In search of molecules displaying ferromagnetic exchange: multiple-decker Ni12 and Ni16 complexes from the use of pyridine-2-amidoxime. Issue 43 (12th October 2016) - Efthymiou, Constantinos G.; Cunha-Silva, Luís; Perlepes, Spyros P.; Brechin, Euan K.; Inglis, Ross; Evangelisti, Marco; Papatriantafyllopoulou, Constantina
Abstract : Ferromagnetic multiple-decker Ni12 and Ni16 clusters consisting of stacked Ni4 layers based on pyridine-2-amidoxime are reported. Abstract : The use of pyridine-2-amidoxime (pyaoxH2 ) in Ni chemistry has provided access to a dodecanuclear complex and a hexadecanuclear Ni cluster, namely [Ni12 (pyaox)6 (pyaoxH)6 (MeOH)2 Cl2 ]Cl4 ·5MeOH (1 ·5MeOH) and [Ni16 (pyaox)8 (pyaoxH)8 (MeOH)4 ](SO4 )4 ·10H2 O·26MeOH (2 ·10H2 O·26MeOH). Complex1 ·5MeOH was isolated by the reaction of NiCl2 ·6H2 O, pyaoxH2 and NaOMe in a 1 : 1 : 2 molar ratio in MeOH in 60% yield. Treatment of NiSO4 ·6H2 O with pyaoxH2 and NEt3 in a 1 : 1 : 2 molar ratio in MeOH afforded2 ·10H2 O·26MeOH in good yield (65%). The two compounds display a multi-decker configuration based on stacked Ni4 layers, Ni4 (pyaox)2 (pyaoxH)2 2+ x ( x = 3, 1 ·5MeOH; x = 4, 2 ·10H2 O·26MeOH); each deck consists of two square planar and two octahedral Ni II centres. The number of decks observed in1 ·5MeOH and2 ·10H2 O·26MeOH depends on the nature of the inorganic anion that is present in the reaction system, which provides elements of synthetic control towards new high nuclearity Ni II species.2 ·10H2 O·26MeOH is the first structurally characterized complex of any metal displaying a quadruple-decker configuration, being also the highest nuclearity metal cluster bearing pyaoxH2 and the highest nuclearity Ni II cluster with any type of 2-pyridyl oxime. Each cluster cation displays ferromagnetic exchange between the octahedral Ni II ions resulting in a spin ground state of S = 6 for1 and S = 8 for2 . Magnetothermal studies have been performed and discussed for both clusters.